2014
DOI: 10.1021/la404884a
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Driven Adsorption and Desorption of Proteins at Solid–Liquid Interfaces

Abstract: The heat-induced desorption and adsorption of the proteins lysozyme, ribonuclease A, bovine serum albumin, and fibronectin at protein layers was investigated in two different environments: pure buffer and protein solution. Using two different environments allows us to distinguish between thermodynamic and kinetic mechanisms in the adsorption process. We observed a desorption in buffer and an adsorption in protein solution, depending upon protein properties, such as size, stability, and charge. We conclude that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…BSA and fibrinogen adsorption on the PET substrate at 37 °C was weaker than that at room temperature. This evidence supports our results in Table 2 and Figure 4 , whereas several studies have indicated contrary results, i.e., that heating enhances protein adsorption on inorganic substrates, including silica and silicon [ 40 , 41 ]. The contradictory effect of temperature on protein adsorption is probably due to the differences in the surface chemistry of plastics and silicon oxide, which has polar groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BSA and fibrinogen adsorption on the PET substrate at 37 °C was weaker than that at room temperature. This evidence supports our results in Table 2 and Figure 4 , whereas several studies have indicated contrary results, i.e., that heating enhances protein adsorption on inorganic substrates, including silica and silicon [ 40 , 41 ]. The contradictory effect of temperature on protein adsorption is probably due to the differences in the surface chemistry of plastics and silicon oxide, which has polar groups.…”
Section: Discussionsupporting
confidence: 92%
“…The degree of adsorption on these surfaces depended on the molecular weight of the proteins. The molecular weights of the proteins that were used in this study are as follows: BSA, 66,300; FN, 440,000 g/mol [ 41 ]. Therefore, the larger FN could be inhibited by steric hindrance from the hydrated and swollen thermoresponsive polymer chains.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of temperature on the amount of adsorbed proteins on silicon wafers was studied for albumin and fibronectin. The adsorbed amount of these proteins remains constant in the range of 20 °C to 40 °C showing no significant desorption [29].…”
Section: Methodsmentioning
confidence: 96%
“…The X-ray reflectivity measurements were performed at the Bl9 beamline at the synchrotron light source DELTA in Dortmund, Germany [31][32][33][34]. We used hard X-rays with a photon energy of 27 keV (0.459 Å) to penetrate the liquid area without loss.…”
Section: In-situ X-ray Reflectivity (Xrr) Experimentsmentioning
confidence: 99%